Wednesday
March 29, 2017

Post a New Question

Posted by on .

Please show the steps and explain how to do this as well.
3√8 · 2√5

  • math - ,

    3 sqrt ( 8 ) * 2 sqrt ( 5 ) =

    3 * 2 * sqrt ( 8 ) * sqrt ( 5 ) =

    6 sqrt ( 8 * 5 ) =

    6 sqrt ( 40 ) =

    6 sqrt ( 4 * 10 ) =

    6 sqrt ( 4 ) * sqrt ( 10 ) =

    6 * 2 * sqrt ( 10 ) =

    12 sqrt ( 10 )

  • math - ,

    thank you so much :)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question